Training, supervision, and experience of coaches offering digital guided self-help for mental health concerns - Fitzsimmons-Craft, Ellen E.; Rojas, Elsa; Topooco, Naira; Rackoff, Gavin N.; Zainal, Nur Hani; Eisenberg, Daniel; Shah, Jillian; Desage, Christina; Wilfley, Denise E.; Taylor, Craig Barr; Newman, Michelle G. (Frontiers in Psychology, 2023)
Accessible, low-cost intervention options are necessary to address the rise in mental health problems among college students. Digital guided self-help, or coached, programs have been developed to provide such services, with many commercially available. As such, there are a large and growing number of individuals coaching these programs. However, an unmet need is to evaluate and assess best practices for training and supervising individuals in these positions. To this end, we describe how we recruited, trained, and supervised coaches as part of a large randomized controlled trial using a widely available digital commercial platform. Coaches were trained to provide digital guided selfhelp for depression, anxiety, and/or eating disorders for college students. Coaches initially attended three live training sessions over 2-3 weeks, viewed multiple training videos, and read a detailed coaching manual developed by our team. Thereafter, they attended weekly supervision. Following their term, coaches completed an exit survey to assess their supervision and training experiences. A total of 37 of 70 (53%) graduate-level student coaches completed the survey. The experience was reported as very positive (95%). In particular, the majority reported feeling well prepared, more confident, and felt they had developed useful skills for their own practice.